Deceptive data? The role of the investigators in the New Survey of London Life and Labour 1928–32. Issue 1 (2nd January 2017) - Abernethy, Simon
ABSTRACT: The data collected by the New Survey of London Life and Labour between 1928 and 1932 is one of the most significant resources of detailed household information for the interwar period, with data extracted for almost 30, 000 households, providing detailed information including birthplaces, hours of work, and wages. This article assesses the process of the original data collection, highlighting issues that mean users of the extracted data must proceed with a measure of caution. In particular, it demonstrates that one investigator employed by the survey, who provided information for around a fifth of households, appears to have regularly submitted generic and estimated information that problematizes the dataset.